Energetic Ion Dynamics in the Perturbed Electromagnetic Fields Near Europa. Issue 9 (17th September 2019) - Breer, Benjamin R.; Liuzzo, Lucas; Arnold, Hannes; Andersson, Peter N.; Simon, Sven
Abstract: We model the dynamics of energetic magnetospheric ions in the perturbed electromagnetic fields near Jupiter's moon Europa. The inhomogeneities in the fields near Europa are generated by the induced dipole field from the moon's subsurface ocean as well as the Alfvénic plasma interaction with its ionosphere and induced field. Inhomogeneities in Europa's ionosphere at various length scales generate substantial asymmetries in the mass loading process that further complicate the structure of the moon's electromagnetic environment. In our study, the electromagnetic fields near Europa are obtained from an established hybrid model, whereas a particle tracing tool is applied to analyze the precipitation of the three most abundant energetic ion species (hydrogen, oxygen, and sulfur) onto the moon's surface at various energies from 1 keV up to 5 MeV. To isolate the contributions of the induced dipole and ionospheric mass loading to the field perturbations and the resulting precipitation patterns, we consider multiple field configurations of successively increasing complexity. For ion energies in the kiloelectron volt regime, magnetic field line draping effectively shields large portions of Europa's surface against energetic ion impacts and drastically alters the shape of the precipitation patterns, compared to uniform fields. The fine structure of these patterns strongly depends on the complexity of the applied ionosphere model. Only in the megaelectron volt regime, the precipitation patterns are qualitatively similar for uniform and draped fields. However, the precipitation of megaelectron volt ions onto Europa is still not homogeneous, since the strong magnetospheric field keeps ion gyroradii much smaller than the moon's radius. Key Points: A combination of hybrid simulations and particle tracing is applied to study the dynamics of energetic magnetospheric ions near Europa Energetic ion dynamics near Europa are strongly affected by the Alfvénic field perturbations near the moon In the kiloelectron volt regime, field line draping due to ionospheric mass loading effectively shields Europa's surface against energetic ions